2019
DOI: 10.5114/hm.2019.79393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and gender in physiological responses, mechanics and performance of master swimmers

Abstract: Purpose. The purpose of the study was to analyse the effects of age and gender in physiological responses, mechanics (stroke frequency, stroke length, stroke index), and performance time of master swimmers. Methods. Overall, 34 male and 25 female master swimmers were divided into 2 age categories: (a) 30-39 years, (b) 40-49 years, and completed a 100-m freestyle swimming test with maximum intensity. Stroke mechanics and performance time were measured during the effort. Blood lactate concentration was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…it was detected that the level of strength had a greater influence on SP in males than in females. this is supported by studies conducted among master swimmers [39], where better values were observed in men compared with women, probably because of the greater muscle mass in males.…”
Section: Discussionsupporting
confidence: 54%
“…it was detected that the level of strength had a greater influence on SP in males than in females. this is supported by studies conducted among master swimmers [39], where better values were observed in men compared with women, probably because of the greater muscle mass in males.…”
Section: Discussionsupporting
confidence: 54%
“…In this case, the first quar-tile was the one with the fastest swimmers and the fourth quartile involved the slowest swimmers. this procedure occurred separately for male and female swimmers because their performances, as expected [31], were significantly different (F(1, 29) = 8.916, p = 0.006). In other words, male and female swimmers were grouped depending on the performance quartiles rather than the absolute values of performance.…”
Section: Discussionmentioning
confidence: 67%